Kegiatan Pemeriksaan Fisik Kesehatan Telinga dalam Rangka Deteksi Dini Otitis Media Supuratif Kronik pada Populasi Lanjut Usia - Mano S, Donatila; Kurniawan, Junius; Alifia, Tosya Putri; Kusuma, Kanaya Fide (Universitas 45 Surabaya, 2024)
Maintaining overall body health, including ear hygiene, is very important. The ear is an important organ in the human balance and hearing system. The human ear has self-cleaning capabilities, facilitated by cerumen, which occurs naturally to protect and keep the ear canal moist. However, too much or too little cerumen production can cause complaints such as decreased hearing, itching, and dry ear canals. Cleaning your ears yourself, which often involves inserting objects into the ear canal, can be dangerous. Improper use of cotton buds can push the cerumen deeper, causing blockages and increasing the risk of injury. This activity employs the PDCA (Plan-Do-Check-Act) method to conduct ear health screening for cerumen and tympanic membranes on 61 participants at the Hana Nursing Home. The physical examination results revealed that we could not assess 6 (9.8%) right tympanic membranes, 8 (13.1%) left tympanic membranes, 19 (31.1%) right ear canals, and 21 (34.4%) right ear canals. The participant's left has prop cerumen. Increased awareness and physical examination of the ear, as early detection can improve ear health and prevent ear injury.